Factors associated with low adherence to medication among patients with type 2 diabetes at different healthcare facilities in southern Bangladesh - Adnan Mannan; Md. Mahbub Hasan; Farhana Akter; Md. Mashud Rana; Nowshad Asgar Chowdhury; Lal B. Rawal; Tuhin Biswas (Taylor & Francis Group, 2021)
Background: Diabetic individuals must adhere to their medications to control their glucose levels and prevent diabetes-related complications. However, there is limited evidence of medication adherence in patients with type 2 diabetes in Bangladesh. Objectives: We assessed the level of adherence and factors associated with low adherence to anti-diabetic medication among patients with type 2 diabetes at different health facilities in southern Bangladesh. Methods: This cross-sectional study included 2,070 patients with type 2 diabetes who presented at five health facilities in the Chittagong Division between November 2018 and June 2019. We assessed medication adherence using a self-reported, structured, eight-item questionnaire and performed multiple logistic regression to investigate the factors associated with low medication adherence. Results: The overall prevalence of low medication adherence was 46.3% (95% CI: 41.4-55.8%) of our study population. Multiple logistic regression analysis revealed that males (OR: 1.37; 95% CI: 1.13-1.67), those with a family income of < 233 USD (OR: 1.54, 95% CI: 1.17-2.03), and those with a diabetic ulcer (OR: 1.42, 95% CI: 1.04-1.94) showed low adherence. Diabetic ulcers, retinopathy, and obesity were relatively more elevated among diabetic patients with low medication adherence. Conclusion: Low medication adherence among patients with type 2 diabetes in southern Bangladesh is a key public health challenge. Factors such as male sex, low annual family income, and diabetic ulcers were associated with low medication adherence. Patient counseling and awareness programs may enhance medication adherence among people with type 2 diabetes. Our findings will help physicians and public health workers to develop targeted strategies to increase awareness of the same among their patients.